MODEL LATIHAN KHUSUS UNTUK MENGURANGI NYERI PADA ICHIALGIA - Alfan Zubaidi; Anissa Eka Septiani; Muh. Syaiful Akbar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2024)
Research on specialised exercise therapy is needed to improve the effectiveness and efficiency in reducing ichialgia pain, which is a painful condition in the buttock area that radiates down the leg, even to the sole of the foot. The pain is often caused by nerve entrapment around the ichiadicus muscle. In the long term, the pain can radiate to both legs and the waist, causing fatigue and impaired function. This study aims to measure the effectiveness of specialised exercise therapy designs in reducing ichialgia pain. This type of research is a Randomised Control Trial (RCT). The study sample was 100 ichialgia patients at Muhammadiyah Karanganyar Hospital. Each group consists of 80 patients. The sampling technique used random sampling. Based on the results of statistical analysis, the Sig. (2 Tailed) of 0.001, which indicates a significant average difference in pain reduction after therapy.